Enhanced probability density function using APD in SAC-OCDMA systems based SPD technique - Al-Khafaji, Hamza M. R.; Aljunid, S. A.; Amphawan, Angela; Fadhil, Hilal A. (2013)
This paper examines the avalanche photodiode (APD) gain impact on spectral-amplitude coding optical code-division multiple-access (SAC-OCDMA) systems based single photodiode detection (SPD) technique. Numerical results are used for inspecting the APD gain influence upon the probability density function (PDF) and signal-to-noise ratio (SNR) performance. The usage of APD over positive-intrinsic-negative (PIN) photodiode accommodates more users with improved PDF and higher SNR.